Management Fertilizer Dosage of Peatland on Plant Conditions and Average Bunch Weight (ABW) of Palm Oil in the Sembilang Dangku Landscape - Rio Octarizza Segara; Hariyadi; Sukarman (International Journal of Engineering and Management Research, 2018)
Palm oil is a prospective crop in the plantation sector. Palm oil is currently contributing large foreign exchange to the country, especially in Indonesia. The problem that occurs is the increase in the area for oil palm plantation development has been limited. One alternative way that can be done is the utilization of neglected marginal land for example peatlands. This research was carried out on the dangku crossing landscape in lowland areas or 5 m above sea level. The results show FFB and ABW have no significant effect on the regression and correlation values at the level of 0.05. The effect of significant difference was shown by the results of average bunch weight (ABW) in T1 treatment, namely the dose of N <1 Kg and P <1.5 Kg which had the highest average compared to T2 and T3 treatments. In addition, fertilizer doses affect plant conditions and visual conditions of plant leaves. The average condition at the location of the planting year which observed normality of the plant was more than 75% with green leaf conditions around 80%. Based on this, it can be explained that fertilizer doses have a good effect on plants in the Sembilang dangku landscape in terms of ABW and plant conditions.